Efektivitas Campuran Zat Pengatur Tumbuh Terhadap Hasil Buah Naga Pada Lahan Pasang Surut - Darma Irawan; Iwan Sasli; Tatang Abdurrahman (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
The study was conducted to determine the effectiveness of a mixture of growth regulators on dragon fruit yields on tidal land, and to determine the best concentration of a mixture of effective growth regulators on dragon fruit yields on tidal land in Dungun Laut Village, Jawai District, Sambas Regency, from July 2021 to August 2021. This study used one-factor Randomized Block Design (RAK) method with 6 levels. Each treatment consisted of 4 samples, in a sample there were 2 fruit treatment samples and each treatment sample was repeated 3 times so total number of samples was 144 samples. The variables observedwere fruit diameter, fruit weight, rind thickness, sucrose content, harvest time, and shelf life. Giving synthetic GA3 as much as 100% cannot be replaced by the mixture of plant extracts on dragon fruit resulting in saline land. Giving 100% synthetic GA3 was able to significant effect on the variables of fruit diameter, rind thickness, fruit weight, harvest time, and shelf life. But it has no significant effect on the fruit sweetness level. The correlation is so close to each observation variables such as fruit weight and rind thickness, fruit weight and harvest time, fruit weight and shelf life, fruit weight and fruit diameter, rind thickness and harvest time, rind thickness and fruit diameter.